Strategies for Improving the Professionalism of Islamic Education Teachers at University - Nor, Asikin; Yusuf, Muhammad; Arabi, Ibnu (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This article aims to explore and improve the professionalism of Islamic Religious Education (IRE) teachers at Lambung Mangkurat University (ULM) by implementing interdisciplinary collaboration strategies. The research method involved in-depth interviews with IRE lecturers at ULM, gaining in-depth insights into implementing cross-disciplinary collaboration to improve professionalism. The surprising research results revealed that cross-disciplinary cooperation is essential in enriching IRE teaching methods beyond conventional boundaries. Integrating disciplines such as psychology, technology, and pedagogy allows for adjustments to students' diverse learning styles, shifting the teaching paradigm to be more holistic, adaptive, and responsive to current educational dynamics. In addition to confirming the need for continuous professional development for educators, this study also identified several challenges that must be overcome to strengthen the professionalism of IRE educators, including financial limitations, insufficient social recognition, and rapid technological development. Recommendations from this study include the development of holistic and technology-based continuing training programs and advocacy to increase social recognition and appreciation of the critical role of IRE educators in facing the growing complexities and demands of modern education.